2021
DOI: 10.3390/su13063346
|View full text |Cite
|
Sign up to set email alerts
|

Public Opinions about Online Learning during COVID-19: A Sentiment Analysis Approach

Abstract: The aim of this study was to analyze public opinion about online learning during the COVID-19 (Coronavirus Disease 2019) pandemic. A total of 154 articles from online news and blogging websites related to online learning were extracted from Google and DuckDuckGo. The articles were extracted for 45 days, starting from the day the World Health Organization (WHO) declared COVID-19 a worldwide pandemic, 11 March 2020. For this research, we applied the dictionary-based approach of the lexicon-based method to perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 38 publications
2
30
0
Order By: Relevance
“…[ 14 ] used TextBlob to perform sentiment analysis towards COVID-19 vaccination by web scraping 154 articles on blogs and online newspapers during the COVID-19 pandemic. They concluded that over 90% of the articles contained positive sentiments towards vaccinations [ 15 ].…”
Section: Related Workmentioning
confidence: 99%
“…[ 14 ] used TextBlob to perform sentiment analysis towards COVID-19 vaccination by web scraping 154 articles on blogs and online newspapers during the COVID-19 pandemic. They concluded that over 90% of the articles contained positive sentiments towards vaccinations [ 15 ].…”
Section: Related Workmentioning
confidence: 99%
“…There have been several works related to analyzing the Twitter dataset on different topics during the COVID-19 pandemic [12][13][14][15]. Only a few studies focus on the Twitter data related to COVID-19 vaccination [16,17].…”
Section: Related Workmentioning
confidence: 99%
“…They aim at identifying the public discussion on addiction on Twitter during the COVID pandemic but have not focused on sentiment analysis on addiction due to the pandemic. In [13], the authors worked with Twitter data related to "Mask". They found that the volume and polarity of mask related tweets has greatly increased during the timeline from 17 March 2020 to 27 July 2020.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…While the majority of studies covered sentiment analysis of COVID-19 tweets in general, some studies put focus on more specific topics, such as vaccination [33,34] or online education [35,36]. There is also a small number of studies that focused more on the comparison of different algorithms for sentiment classification of COVID-19 tweets than on their application and analysis of results.…”
Section: Nlp-based Analyses Of Covid-19 Related Tweetsmentioning
confidence: 99%